Unveiling the Future of Sustainable Connectivity: A Comprehensive Review of Solar Cell Radio Wave Hybrid Systems - Sawera Hafeez (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Abstract A paradigm shift that could change the way we think about energy production, wireless communication, and sustainability has been brought about by the combination of solar cell technology and radio wave communication. This article examines the numerous effects of solar cell radio wave hybrid systems in a variety of contexts, including wireless sensor networks, smart cities, medical applications, and more. These hybrid systems enable self-powered devices, networks, and infrastructures to run independently, improve dependability, and aid in environmental preservation by capturing energy from both ambient radio frequency (RF) signals and sunlight. The fundamentals of radio wave transmission, energy harvesting, and the complex interplay between solar cell technology and RF communication are all covered in detail in this study. The possible uses of solar cell radio wave systems are clarified through a variety of case studies, demonstrating their influence on sectors like agriculture, smart infrastructure, environmental monitoring, and emergency response. The paper discusses the difficulties in putting these systems into practice, such as frequency spectrum limitations, material compatibility, and energy harvesting effectiveness. Additionally, it investigates new developments and directions that show promise for the advancement of solar cell radio wave integration. The study shows the ongoing innovation that will progress the industry, from cutting-edge energy harvesting methods and the development of 5G connectivity to flexible and wearable applications. It also emphasizes how crucial ethical and environmental factors are when using these technologies. The report concludes by summarizing the significant implications of solar cell radio wave hybrid systems and framing them as a portal to a more connected, environmentally friendly, and technologically advanced future.